Media Implementation SPIN GAME SCIENCE SMART (SGSS) on the Material of Vibration On the Level of Student Motivation and Learning Outcomes In the Pandemic Era - Hayati, Muriani Nur; Nur, Aprilia; Fatkhurrohman, M. Aji (PSEJ (Pancasakti Science Education Journal), 2023)
The history of the world of education began to occur in 2020 when learning activities were carried out online. This situation has a major impact on the implementation of learning, especially in the use of learning media. The purpose of this study was to determine the level of student learning motivation when learning online using SGSS media and without SGSS media in the pandemic era and to find out the differences in student learning outcomes using SGSS media and without SGSS media in online learning. Data collection techniques using test techniques, interviews, documentation and questionnaires. Data were analyzed by descriptive analysis and independent sample t test. The results average value motivation experimental class was 83.64 in the very good category while the control class was 79.53 in the good category and the results of the independent sample t test showed a sig (2-tailed) value of 0.457 or greater from 0.05 so that it can be concluded that student learning outcomes between using SGGS media and without SGSS media don’t provide a significant difference. The use of SGSS media needs to be followed up both online and offline.